2021
DOI: 10.1177/2045125320982720
|View full text |Cite
|
Sign up to set email alerts
|

Current antipsychotic agent use and risk of venous thromboembolism and pulmonary embolism: a systematic review and meta-analysis of observational studies

Abstract: Background: Antipsychotic agents (APS) are widely used drugs to treat psychotic symptoms and can effectively reduce both positive and negative symptoms of schizophrenia. For decades, some studies suggested that there is a relationship between using APS and the risk of venous thromboembolism (VTE) and pulmonary embolism (PE). However, results remain inconclusive. Method: This review has been registered in International Prospective Register of Systematic Reviews (PROSPERO, ID: CDR42020155620). Relevant studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 64 publications
1
35
0
Order By: Relevance
“…A large US hospital database of 28,723,711 adults in 2006 demonstrated that the risk of PE was greater in antipsychotic users than in the total population ( p < 0.001), and clozapine in higher doses was associated with the greatest risk amongst all antipsychotics 11 . Meta‐analyses of observational studies have also reported significantly increased risks of PE in antipsychotic users, particularly in previously antipsychotic‐naive patients 14‐16 . Therefore, it is important to be aware of this rare but significant adverse effect.…”
Section: Discussionmentioning
confidence: 99%
“…A large US hospital database of 28,723,711 adults in 2006 demonstrated that the risk of PE was greater in antipsychotic users than in the total population ( p < 0.001), and clozapine in higher doses was associated with the greatest risk amongst all antipsychotics 11 . Meta‐analyses of observational studies have also reported significantly increased risks of PE in antipsychotic users, particularly in previously antipsychotic‐naive patients 14‐16 . Therefore, it is important to be aware of this rare but significant adverse effect.…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanisms of this phenomenon may be attributed to that the hypercoagulable state induced by drugs through increasing platelet aggregation and antiphospholipid antibodies, hyperprolactinemia and metabolic disturbance [12,16]. However, a recent study showed that some individual drugs, such as quetiapine or aripiprazole, were not associated with the risk of VTE [27]. Selective serotonin reuptake inhibitor and serotonin norepinephrine reuptake inhibitors were also unlikely to contribute to VTE because of their potent inhibitory effects on the 5-hydroxytryptamine (5-HT) transporter to attenuate platelet activation and weaken the risk of thromboembolism formation [28].…”
Section: Discussionmentioning
confidence: 99%
“…This patient had several risk factors for developing PE that were overlooked by the physicians, including old age, being overweight, having hypertension, and prolonged limited mobility owing to dementia. Recent studies have also linked the current use of antipsychotics with the development of PE (7). As mentioned earlier, the patient had been using risperidone for two years before admission which may have increased the risk of PE.…”
Section: Case Presentationmentioning
confidence: 95%